Subarachnoid haemorrhage as a late complication of infective endocarditis: a case report - T. Samarawickrama; T. A. S. L. Karunarathna; B. G. D. S. Govindapala; M. M. P. T. Jayasekara; R. Sirimanna; R. A. N. K. Wijesinghe; A. I. Biyanwila (Sri Lanka College of Internal Medicine, 2022)
Rupture of an infectious intracranial aneurysm causing subarachnoid haemorrhage is a rare complication of infective endocarditis. We report a case of subarachnoid haemorrhage that occurred as a late complication, in an infective endocarditis patient, on the 30th day of successful treatment, which is an extremely rare occurrence. He was a mainline drug addict with a history of rheumatic valvular heart disease.